#TITLE_ALTERNATIVE# - SUSILAWATI (NIM 10103039), EKA
Mahalanobis distance is a distance base on correlation structure between variable which have different shape that can be identified and analyzed. Mahalanobis distance usually used in cluster analyzation, outlier identification an another classification. Outlier identification method is still being a focus for efficiency improvement. In this final project, the author try to present it base on literature and simulation. Determinan methode have a same effctivity but have a better effecience than MVV (Minimum Vector Variance) method. In this research the author use Normal datas with many variation of size data.